Effect of Age on Conversion to Everolimus with Calcineurin Inhibitor Minimization at A Late Post-Transplant Stage - Uchida, Junji; Nishide, Shunji; Kabei, Kazuya; Shimada, Hisao; Kosoku, Akihiro; Iwai, Tomoaki; Kuwabara, Nobuyuki; Naganuma, Toshihide; Kumada, Norihiko; Takemoto, Yoshiaki; et al. (Urology Journal, 2018)
Purpose: The purpose of this study was to identify the risk factors for everolimus discontinuation in kidney transplant recipients converted to everolimus with calcineurin inhibitor (CNI) minimization at a late post-transplant stage. Materials and Methods: An observational retrospective cohort study was conducted on a total of 38 recipients of kidney transplantation at our institution from June 2012 to March 2015 who were converted from antimetabolites to everolimus at a late post-transplant stage and followed for 1 year. We divided the patients into two groups to evaluate the factors affecting everolimus discontinuation after conversion: everolimus continuation group (n = 23), patients in whom everolimus maintained, and everolimus discontinuation group (n = 15), patients in whom everolimus were stopped within 1 year after conversion. Results: Age at conversion was significantly older in the everolimus discontinuation group compared to the everolimus continuation group (57.9 ± 12.0 years in the everolimus discontinuation group vs 45.7 ± 11.2 years in the everolimus continuous group; P = .0062). Multivariate cox proportional hazard regression analysis revealed that age at conversion significantly correlated with everolimus discontinuation (P = .012). Receiver operating characteristic curve of age at conversion showed that the cut-off value was 55 years old for the everolimus discontinuation group [area under curve 0.804, 95% confidence interval (0.654-0.954), sensitivity 86.7%, specificity 65.2%]. Conclusion: Our results indicated that late conversion to everolimus with CNI minimization in elderly recipients older than 55 years of age may be associated with more frequent adverse events and discontinuations.